PENGARUH KEPEMILIKAN MANAJERIAL DAN LEVERAGE TERHADAP NILAI PERUSAHAAN (STUDI PADA PERUSAHAAN INDUSTRI KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015 SAMPAI DENGAN 2018) - Rahmadita, Yuriza; Makhdalena, Makhdalena; Kartikowati, Rr Sri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aimed to investigate the effect of managerial ownership and leverage on the firm value. The population in this study are all chemical industry companies listed in the Indonesian Stock Exchange that have data (managerial ownership, leverage and firm value) years 2015 until 2018. This research used secondary data. Data collection techniques used documentation techniques. The data analysis technique used in this research is path analysis. These results indicate that managerial ownership and leverage simultaneously and partially affect the firm value.Key Words: Managerial ownership, Leverage, Firm Value